Application of cycling gradient capillary electrophoresis to detection of APC, K-ras, and DCC point mutations in patients with sporadic colorectal tumors - Minarik, Marek; Minarikova, Lucie; Hrabikova, Michala; Minarikova, Petra; Hrabal, Petr; Zavoral, Miroslav (Electrophoresis, 2004)
A previously introduced technique of cycling gradient capillary electrophoresis (CGCE) was applied to monitoring of molecular changes during adenoma-carcinoma transition in progression of sporadic colorectal cancer. The purpose of this work was optimization of separation parameters for selected mutation regions in tumor suppressor genes involved in the early stages of colorectal carcinogenesis, followed by scanning for these mutations in clinical tissue samples from patients with adenomatous polyps and early carcinomas. A total of 47 colorectal tumors in various stages of progression were examined. Main emphasis was given to evaluation of mutation detection sensitivity and specificity required for effective early disease detection. A total of 7 different somatic mutations was identified among 32 K-ras mutant samples, 1 inherited mutation and 5 somatic mutations were identified among 15 adenomatous polyposis coli (APC) mutated samples. None of the two previously reported "deleted in colorectal carcinomas" (DCC) mutations was found in any of the clinical samples. In addition to simple optimization of running conditions, CGCE has demonstrated sensitivity and selectivity allowing detecting small mutant fractions as well as combination of multiple mutants within a single target sequence.
Keywords: geny ras; Colorectal Neoplasms; geny DCC; bodová mutace; kolorektální nádory; Base Sequence; DNA Primers; lidé; geny APC; Point Mutation; Genes, DCC; Genes, APC; DNA primery; Genes, ras; sekvence nukleotidů; Humans